Pembuatan Peta Online Obyek Wisata dengan Google My Maps - Sukadi (Jurnal Qua Teknika, 2023)
This research is motivated by current technological advances, especially information technology which has been able to change people's habits in their daily activities. Starting from business information processing activities, education, to the process of fulfilling daily needs that can be met with internet technology. In this study, an online map of tourist objects was created with Google My Maps with sample data, namely tourist objects in Pacitan Regency. The results of this study are an online map of tourist objects in Pacitan Regency which can be used as a promotional medium in accordance with current technological advances, and also with this Online Map it is hoped that it can increase the number of tourist visits to Pacitan Regency which will increase local revenue. from the tourism sector